DBEM crack propagation in friction stir welded aluminum joints. (November 2016) - Citarella, R.; Carlone, P.; Sepe, R.; Lepore, M.
Abstract: This paper deals with the simulation of multiple crack propagation in friction stir welded butt joints and the aim is to assess the influence of process induced residual stresses on the fatigue behavior of the assembly. The distribution of the process induced residual stresses is mapped by means of the contour method; then, the computed residual stress field is superimposed, in the DBEM environment, to the stress field due to a remote fatigue traction load and the crack growth is simulated. A two-parameters crack growth law is used for the crack propagation rate assessment. The Stress Intensity Factors are evaluated by the J-integral technique. Computational results have been compared with experimental data, provided by constant amplitude crack propagation tests on welded samples, showing the subdivision of the overall fatigue life in the two periods of crack initiation and crack propagation.